ANTHROPOLOGICAL STUDY OF SAMPURAGA FOLK STORY IN WEST PANYABUNGAN - Kusor Kusor (JURNAL DARMA AGUNG, 2022)
This study describes of the antropological study of sampuraga folk story in west panyabungan. The purpose of this study was to elaborate anthropology study of folk story of sampuraga. This study finds out the relation between anthropology study and folk story of sampuraga. This study used descriptive method with a qualitative approach. The focus of this study was on anthropology study and folk story of sampuraga. Anthropology is the science that studies human beings. Starting from evolution, communication, socialization, to human adaptation to their environment. Anthropology uses humans as subjects and objects of study in its science. All of these complicated activities are carried out with the aim of finding out the most appropriate answer to curiosity about human existence, how humans appeared and in what way. Not limited to the human past, but also predictions about the future of human life. The findings of this study show that sampuraga folk story has related with anthropological study.